Mammoth backlog of court cases pending in India: A spatial visualisation - Sugam Agarwal; Smruti Ranjan Behera (Regional Studies, Regional Science, 2024)
The judiciary plays a pivotal role in maintaining the rule of law and protecting the fundamental rights of citizens, pledging the efficient enforcement of rules and regulations and upholding civil and criminal justice in principles. The judicial system in an emerging economy like India must ensure timely and equitable justice for all citizens. For more than the last thirty years, the Indian judiciary has been facing colossal pendency levels and long case processing times. Against this backdrop, this paper visualises the spatial variations in the number of unresolved court cases in different districts of India in 2023. The spatial visualisation using a cartogram map elucidates some specific districts in certain Indian states, based on their population, that are now awaiting huge court proceedings. The spatial variations in pending cases across different regions emphasise the need for deliberate initiatives to promote regional justice by maximising the number of pending cases to be disposed of as soon as possible. The visualisation analysis validates that for the smooth functioning of overburdened pending court proceedings and to maximise the number of cases disposed, the judicial system needs substantial reforms, upgradation of massive court infrastructure, required reallocation and recruitment of judges and court staff, especially in high-density populated areas like New Delhi and Mumbai metropolitan cities in India. Therefore, this finding suggests that a massive backlog of pending court and overburdened cases knowledge is critical for state governments seeking to increase judicial efficiency by focusing on districts with a high volume of pending cases.